Say it like Goethe: Language learning facilities abroad and the self-selection of immigrants - Philipp Jaschke; Sekou Keita (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
Immigration policy in most high-income countries is designed to promote qualified migration while maintaining high requirements on characteristics such as education and language skills. We rely on a standard self-selection model with heterogeneous migration costs to discuss the effect of access to language learning services in the country of origin on the skill composition of immigrants in Germany. Using individual-level survey data on immigrants from different cohorts over the period 2000 - 2014, combined with unique data on the presence of Goethe Institutes - a German association promoting German language and culture worldwide - in origin countries, the results of our empirical analysis show that the acquisition of the German language is fostered by the availability of language courses abroad. Moreover, we find that language services abroad induce a positive (self-)selection of migrants along several dimensions, such as education, experience, and the probability of holding a job offer at arrival. These characteristics are in turn highly relevant for long- term integration in Germany. To disentangle transmission channels, we perform a causal mediation analysis. We find that 25 % of the total effect of language services abroad on language skills at immigration trace back directly to migrants' participation in language courses, revealing important spillover effects. – – Die Einwanderungspolitik in den meisten einkommensstarken Ländern zielt darauf ab, qualifizierte Migration bei gleichzeitiger Beibehaltung hoher Anforderungen an Bildung und Sprachkenntnisse zu fördern. Wir verwenden ein etabliertes theoretisches Modell zur Selbstselektion von Migrantinnen und Migranten mit heterogenen Migrationskosten, um die Auswirkungen des Zugangs zu Sprachlernangeboten im Herkunftsland auf verschiedene Qualifikationen von Migrantinnen und Migranten in Deutschland zu untersuchen. Ausgehend von individuellen Befragungsdaten von Zugewanderten aus Kohorten zwischen 2000 und 2014, kombiniert mit neu vorliegenden Daten über die Präsenz von Goethe Instituten in den Herkunftsländern, zeigen unsere Ergebnisse, dass der Erwerb der deutschen Sprache durch die Verfügbarkeit von Sprachkursen im Ausland gefördert wird. Darüber hinaus stellen wir fest, dass Sprachlernangebote im Ausland eine positive (Selbst-)Selektion von Migrantinnen und Migranten entlang mehrerer Dimensionen bewirken, wie z.B. Bildung, Erwerbserfahrung und die Wahrscheinlichkeit eines Stellenangebots bei Einreise. Diese Eigenschaften sind wiederum für die langfristige Integration in Deutschland von großer Bedeutung. Zur Identifikation von Wirkungskanälen, führen wir eine kausale Mediationsanalyse durch. Es zeigt sich, dass 25 % des gesamten Effekts durch angebotene Sprachkurse im Ausland auf die Sprachkenntnisse zum Zeitpunkt der Einwanderung direkt auf die Teilnahme von Migrantinnen und Migranten an Sprachkursen zurückzuführen sind. Dies deutet auf substantielle Spillover-Effekte hin.
Keywords: F22; J18; J24; J61; Z13; 330; International Migration; Public Policy; Human Capital - Skills; Immigrant Workers